Development of a fully automated low‐pressure [11C]CO carbonylation apparatus. (27th August 2020) - Ferrat, Mélodie; El Khoury, Youssef; Larsen, Peter; Dahl, Kenneth; Halldin, Christer; Schou, Magnus
Abstract : [ 11 C]carbon monoxide ([ 11 C]CO) is a versatile synthon for radiolabeling of drug‐like molecules for imaging studies with positron emission tomography (PET). We here report the development of a novel, user‐friendly, fully automated, and good manufacturing practice (GMP) compliant low‐pressure synthesis module for 11 C‐carbonylation reactions using [ 11 C]CO. In this synthesis module, [ 11 C]CO was reliably prepared from cyclotron‐produced [ 11 C]carbon dioxide ([ 11 C]CO2 ) by reduction over heated molybdenum and delivered to the reaction vessel within 7 min after end of bombardment, with an overall radiochemical yield (RCY) of 71%. [ 11 C]AZ13198083, a histamine type‐3 receptor ligand, was used as a model compound to assess the functionality of the radiochemistry module. At full batch production conditions (55 μA, 30 min), our newly developed low‐pressure 11 C‐carbonylation apparatus enabled us to prepare [ 11 C]AZ13198083 in an isolated radioactivity of 8540 ± 1400 MBq ( n = 3). The radiochemical purity of each of the final formulated batches exceeded 99%, and all other quality control tests results conformed with specifications typically set for carbon‐11 labeled radiopharmaceuticals. In conclusion, this novel radiochemistry system offers a convenient GMP compliant production drugs and radioligands for imaging studies in human subjects. Abstract : Automated 11 C‐carbonylation module allowed for GMP production of AZ13198083 in high radiochemical yield and purity.